The Molecular Detection and Therapeutic Management of Pathogenic Theileria luwenshuni Infection in a Goat: A Case Report - Syed Abdul Arif; Deepa Lahkar; Sophia Makdoh Gogoi; Bendangla Changkija; Parikshit Kakati; Lukumoni Buragohain; Mamta Pathak; Tinku Das (Iranian Journal of Parasitology, 2024)
A 2-year-old female Assam Hill goat was presented with a clinical history of anorexia, fever, mild anemia, rough body coat, dehydration, tachycardia, dyspnea and swelling of palpable lymph nodes. Hematology revealed low hemoglobin, packed cell volume, red blood cell and thrombocyte count. Biochemical analysis showed increased serum concentration of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatinine and urea in comparison to the normal reference range. Microscopic examination showed intra-erythrocytic forms of Theileria species. Molecular and phylogenetic analysis of partial 18S rRNA gene sequence confirmed Theileria luwenshuni infection. The goat was treated with buparvaquone and oxytetracycline and recovered uneventfully. A three-month follow-up showed no recurrence. This study reveals the presence of T. luwenshuni in Assam, India and it should be considered in differential diagnosis and as one of the important pathogens of clinically sick goats. The present case report provides a rational approach to diagnosis and treatment for a goat infected with pathogenic T. luwenshuni in Assam, India. To our knowledge, the present communication describes about the first successful therapeutic management of pathogenic T. luwenshuni infection in a goat supported with molecular evidence from Assam, a north-eastern state of India.